Building Belonging through Art with Young Migrants Living in Care in South Africa - Shahrokh, Thea; Treves, Giulia (African Human Mobility Review, 2021)
As young people with migration experiences build their lives in new contexts, theirconnectedness to who they are, to other people, to place and to culture underpinwhether and how a sense of belonging is built in their lives. Belonging as a conceptmatters in young lives as it is underpinned by feelings of acceptance, inclusion and selfdetermination.The realization of belonging can have important implications for youngpeople’s wellbeing and development. This paper shares the barriers to belonging foryoung migrants in South Africa, and how the pain of past experiences, and the exclusionsthey are navigating in the present constrain their sense of agency, impacting selfworthand relationship formation. We share how a child and youth care center in CapeTown specializing in supporting young migrants and young people with experiencesof trauma, innovated with a group of young women through participatory arts-basedmethods towards building belonging. We found that layering multiple arts methodscan support young people to connect to their cultural roots and personal relationships,re-build trust, reimagine their identities as part of a collective and challenge powerrelations around gender, nationality and generation. We found that building belongingshould be seen as a continuous learning process, that builds young people’s reflectivecapacities to understand self and others and to make sense of the interaction betweenpast, present and future. In turn, belonging provides an important conceptual tool foryouth-led, context-specific approaches to working with young migrants, including onyouth transitions.